Analysis of salivary level Lactobacillus spp. and associated factors as determinants of dental caries amongst primary school children in Harar town, eastern Ethiopia - Dawit Ademe; Desalegn Admassu; Senthilkumar Balakrishnan (BMC, 2020)
Abstract Background Lactobacillus spp. play a major role in the development of dental caries. Although effective methods are known for the prevention and management of dental caries, its prevalence of dental caries is increasing amongst school-age children in Ethiopia. Hence, this study is aimed to determine the association of salivary Lactobacillus spp. level and oral health factors as determinants of dental caries amongst primary school children in Harar town, Eastern Ethiopia. Methods A cross-sectional study was conducted amongst primary school children (n = 407) using a questionnaire survey, clinical DMFT (decayed, missing, filled tooth number) examination and enumeration of salivary level Lactobacillus spp. Data were analyzed by SPSS (Statistical Package for Social Science software- version 25.0). The odds ratio was used to determine the predictors of the outcome. The data were expressed as mean ± SD. Statistical significance was defined as a p-value of less than 0.05. Results The prevalence of dental caries was found to be 36.9% amongst primary school children. The mean DMFT value of the participants was 0.95 ± 1.57. The dental decay component was the primary observation that accounted for 84.6% of the DMFT. Almost, 67% of the saliva culture revealed a significant amount of Lactobacillus spp. count. The mean bacterial count was found to be 14.92 × 105 ± 22.92 × 105. Among various parameters analysed for association with dental caries, a number of them show positive associtation, incluing reduction in academic scores in the prevous academic year (p = 0.034), grade levels of school children 1-4 (p = 0.041), sweet food consumption habit (p = 0.003), absence of daily teeth cleaning habit (p = 0.002), absence of toothpaste use (p = 0.001), dental ache history (p = < 0.001), significant microbial load of salivary Lactobacillus spp. (p = < 0.001), acidic (p = 0.028) and basic salivary pH (p = 0.025). Conclusion A significant salivary Lactobacillus count associated with lower grade level, sweet diet, and poor oral hygiene were found to be the determinant factors for dental caries. Thus, dissemination of oral health information is obligatory to prevent dental caries amongst primary school children in the study area.